Funerary practices in Serbia - Pavićević, Aleksandra (Funerary international, 2021)
Funerary Practices in Serbia is the first book to offer a concise yet highly informative study of the historical development and current state of funerary practices in Serbia. Situated in a constant dynamic struggle between traditional cultural customs and modern legislation, funerary practices in Serbia represent a particularly interesting field of research. In this study, Pavićević combines an investigation of long-term developments and recent changes to place contemporary practices in their wider historical context, emphasizing the complicated geo-political, demographic and cultural factors that have shaped funeral traditions in Serbia over time. In particular, she demonstrates how the country's frequent changing of borders and life under the rule of two great empires - the Austro-Hungarian and Ottoman - fostered the emergence of colorful funerary traditions, such as open-casket burial and vigils around the body, that persist to this day in spite of government attempts to modernize funerary practice since the end of the 19th century. The book also provides illuminating insights into the legal framework surrounding current funerary practices in Serbia, the relationship between the state and private sectors, the ownership of cemeteries and gravesites, the role of churches and religious communities, religious and ethnic variations in funerary culture and traditions, and the development of modern cremation practices in Serbia. This book provides a useful and original resource for policymakers and practitioners interested in the historic, legal, technical and professional aspects of the Serbian funerary industry, and to researchers in cultural anthropology, history, sociology and cultural management.